Evaluation of Some Immunological Parameters in with Men Diabetic Nephropathy - Al-Haddad, Senan Abd Al-Razaq; Jwad, Saher Mahmood (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The Aim: The study aims to the possibility of depending on some immunological criteria (monocyte chemoattractant protein (MCP-1, MCP-3) and interleukin-18). Study Design: The study is indicators for early diagnosis of diabetic nephropathy in patients with type 2 diabetes and avoiding its development to advanced stages. Place and Duration of Study: Endocrinology Center / Al-Sadr Medical City and also Al-Manathira General Hospital / Al-Najaf Governorate, their ages ranged between (30- 60) years old, and the study continued for the period from 1/10/2022 to 31/3/2023 after obtaining the consent of the two study groups. Methodology: The study included the follow-up of (90) men, (30) healthy individuals and (60) patients with type 2 diabetes mellitus to periodic clinical examination ,the estimation of glycosylated hemoglobin ratio (HbA1c) and evaluation of immunological parameters represented in levels of monocyte chemoattractant protein (MCP-1 , MCP-3 ) and interleukin-18 . Results: The study diagnosed a significant increase (P < 0.05) in glycosylated hemoglobin ratio, monocyte chemoattractant protein MCP-1, MCP-3) and interleukin-18 ,and in contrast to a significant decrease (P < 0.05) in the glomerular filtration rate (GFR) in men with diabetes mellitus type II compared to healthy men. The study also showed a significant effect (P < 0.05) for the age groups on the glycosylated hemoglobin ratio and monocyte chemoattractant protein (MCP-3), and conversely a significant decline in the glomerular filtration rate (GFR) ,while no significant differences appeared (P > 0.05) in levels of monocyte chemoattractant protein (MCP-1) and interleukin-18. Also, a notable impact (P < 0.05) was observed for the duration of diabetes mellitus on the levels of monocyte chemoattractant protein (MCP-1 , MCP-3 ),whereas no substantial differences appeared (P > 0.05) in levels of glycosylated hemoglobin ratio, glomerular filtration rate (GFR) and interleukin-18. In addition to the foregoing, the trial recorded a significant influence (P < 0.05) of body mass index on the levels of monocyte chemoattractant protein (MCP-3),while no noticeable differences appeared (P > 0.05)in, the glycosylated hemoglobin ratio , glomerular filtration rate(GFR),and monocyte chemoattractant protein (MCP-1). Moreover, a significant effect (P < 0.05) for stages of diabetic nephropathy was diagnosed on the glycosylated hemoglobin ratio, monocyte chemoattractant protein (MCP-1, MCP-3), interleukin-18 and glomerular filtration rate (GFR). Conclusion: It is possible to depend on the increased levels of some immunological indicators especially MCP-1, MCP-3 and interleukin-18 as predictive biomarkers to diagnose the progression to advance stages of the diabetic nephropathy if this coincides with a decrease in the glomerular filtration rate.